A method for preparing tin plating additive

By building a three-layer functional synergistic structure and using functional polymers and materials, the shortcomings of traditional plating additives in structural design and performance control are solved, and the overall improvement of plating performance is achieved, which significantly improves binding force, uniformity and corrosion resistance.

CN119776923APending Publication Date: 2025-04-08DONGGUAN CUYU NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411961159.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Traditional tin plating additives have shortcomings in structural design and performance control, resulting in insufficient density of the coating structure, unstable quality, difficulty in taking into account uniformity and fine crystallization characteristics, and poor process adaptability, affecting production efficiency and product quality.

Method used

By building a three-layer functional synergistic structure of the intelligent response layer, the self-assembled guide layer and the interface regulation layer, the comprehensive improvement of the coating performance is achieved by using functional polymers and materials such as PNIPAM, PAA, PANI, surfactant, silane, PAMAM dendrimers and sulfonated graphene.

Benefits of technology

It significantly improves the bonding force, uniformity and corrosion resistance of the coating, reduces the rework rate, extends the service life, and has good process adaptability and economic benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The method of the present invention discloses a method for preparing a tin plating additive. The present invention realizes a comprehensive improvement in the performance of the coating by constructing a three-layer functional synergistic structure. The innermost intelligent response layer is composed of PNI PAM, PAA and PANI, which respectively realize temperature response regulation, chemical bonding and conductive network construction; the middle self-assembly guiding layer combines surfactants and silane coupling agents to form an ordered assembly and chemical pin positioning points; the outermost interface regulation layer uses PAMAM dendritic molecules and sulfonated graphene to provide coordination sites and conductive networks. This three-layer structural design significantly improves the bonding force, uniformity and anti-corrosion performance of the coating. The product has the advantages of stable process, reliable raw materials, and production compatibility. It can be widely used in multiple industrial fields and has significant economic benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of chemical technology, and in particular to a preparation method of a tin plating additive and a preparation method thereof. Background Art

[0002] As an important metal surface treatment process, tin plating technology occupies a key position in the fields of electronics, food packaging, welding, etc. This technology provides conductivity, solderability and corrosion protection by depositing a layer of tin coating on the surface of the base metal, and has a history of industrial application of nearly a hundred years. At present, the tin plating process is widely used in printed circuit boards, electronic components, tinplate packaging, welding pretreatment and other fields, and the global output value continues to grow every year. According to the different deposition mechanisms, the tin plating process can be divided into hot-dip tin plating, electroplating tin plating and chemical tin plating. Among them, electroplating tin has become the most commonly used tin plating method due to its advantages such as uniform coating, controllable thickness and moderate cost.

[0003] In the traditional electroplating tin process, the additive system plays a decisive role in the quality of the coating. Such additives are usually composed of multiple functional components such as levelers, brighteners, antioxidants and stabilizers. Among them, levelers mainly include organic compounds such as alkyl sulfonic acids and imidazoles, which regulate the deposition behavior of tin ions through selective adsorption; brighteners often use aromatic aldehydes, ketones and other compounds to improve the surface gloss of the coating; antioxidants are used to prevent the oxidation of stannous ions and maintain the stability of the plating solution; stabilizers are mainly used to complex excess metal ions to prevent spontaneous decomposition. These components affect the reduction and deposition process of metal ions by forming a complex adsorption layer at the electrode interface, thereby achieving the regulation of the coating performance.

[0004] However, with the rapid development of the electronics industry and the increasing trend of product miniaturization, many deficiencies of traditional tin plating additives have become increasingly prominent. First, in terms of structural design, existing additives mainly rely on simple physical adsorption and lack a stable chemical bonding mechanism. This single interface action mode cannot form a multi-level protective structure, and the interaction between the components is weak, making it difficult to produce a significant synergistic effect. The resulting coating structure is not dense enough, and defects such as coarse grains, pinholes and cracks often occur, which seriously affects the solderability and reliability of the product. Secondly, in terms of performance control, traditional additives lack the ability to respond to fluctuations in process parameters such as temperature and acidity during the electroplating process, and cannot achieve real-time regulation, resulting in poor batch stability of the coating quality. At the same time, due to the lack of a systematic interface regulation mechanism, it is difficult for existing additives to simultaneously take into account the uniformity and fine crystallization characteristics of the coating, and often there are contradictory phenomena such as increased brightness but decreased bonding, or improved solderability but uneven distribution.

[0005] Even more thorny is the problem of process adaptability. Most traditional tin plating additives have poor stability under acidic conditions, are prone to decomposition, and have insufficient control over the redox balance of stannous ions. Roughness and scorching are likely to occur under high current density conditions, and performance degradation is obvious during long-term use, requiring frequent replenishment and maintenance. Additive products from different manufacturers have poor compatibility with each other, and process parameters often need to be re-adjusted when changing products, which not only increases production costs but also affects production efficiency. In addition, as electronic products develop towards high-density interconnection, higher requirements are placed on the microstructure and interface characteristics of the coating, and traditional additives can no longer meet the needs of new packaging technologies. Summary of the invention

[0006] In order to solve or partially solve the problems existing in the related art, the first aspect of the present invention application provides a method for preparing a tin plating additive, comprising the following steps:

[0007] S1 Raw material preparation and inspection

[0008] Use an analytical balance to weigh the required raw materials: analytical pure stannous chloride, potassium chloride, and boric acid. Prepare deionized water with a conductivity of 0.05-0.15 μS / cm, and prepare functional components: PNIPAM powder with a molecular weight of 18000-22000, PAA aqueous solution with a mass fraction of 38-42%, doped PANI conductive powder, dodecyl dimethyl betaine, γ-aminopropyl triethoxysilane, PAMAM dendrimers, and sulfonated graphene powder with an oxidation degree of 28-32%;

[0009] S2 basic plating solution preparation

[0010] Clean and dry the 10L preparation tank. First, measure 4.8-5.2L of deionized water into the preparation tank. Turn on the agitator, adjust the speed to 280-320rpm, slowly add 380-420g of stannous chloride, observe the dissolution, and stir for 8-12 minutes until it is completely dissolved. Continue to add 950-1050g of potassium chloride, keep stirring at the same speed for 13-17 minutes, and after the potassium chloride is completely dissolved, add 130-150g of boric acid, continue stirring for 18-22 minutes until the solution is clear and transparent, and finally use deionized water to make up to 7.8-8.2L, and filter through a 0.45μm filter membrane to remove insoluble matter; the entire preparation process should be carried out at room temperature, and the dissolution should be observed regularly to avoid local precipitation;

[0011] S3 intelligent response system preparation

[0012] First, prepare the PNIPAM solution: prepare a 500 mL beaker, weigh 4.6-5.0 g of PNIPAM powder, slowly add 480-520 mL of deionized water, use a constant temperature magnetic stirrer to stir and swell at 190-210 rpm for 1.8-2.2 hours at room temperature. After swelling, transfer the solution to an ultrasonic processor and ultrasonicate at a frequency of 38-42 kHz for 28-32 minutes;

[0013] Next, prepare the PAA solution: Use a pipette to accurately measure 9.5-10.5 mL of PAA stock solution, slowly drop it into a beaker containing 470-510 mL of deionized water, and stir with a magnetic stirrer for 13-17 minutes until the solution is uniform and transparent;

[0014] Finally, PANI dispersion was prepared by weighing 3.0-3.4 g PANI powder, transferring it into a beaker containing 380-420 mL deionized water, and treating it with an ultrasonic disperser at a frequency of 38-42 kHz for 43-47 minutes, during which the dispersion state was observed every 15 minutes;

[0015] Preparation of S4 self-assembly guiding system

[0016] Preparation of surfactant solution: weigh 3.8-4.2 g of dodecyl dimethyl betaine, add 380-420 mL of deionized water, place the solution in a constant temperature water bath, control the temperature at 38-42 ° C, start the stirrer and stir for 18-22 minutes until the solution is completely clear;

[0017] Preparation of silane solution: In a fume hood, use a pipette to accurately measure 3.8-4.2 mL of γ-aminopropyltriethoxysilane, slowly drop it into 375-415 mL of anhydrous ethanol, adjust the stirrer speed to 140-160 rpm, and stir for 28-32 minutes for hydrolysis. During this period, pay attention to observe the state of the solution to avoid local gelation;

[0018] Preparation of S5 interface regulation system

[0019] Preparation of dendrimer solution: Weigh 4.6-5.0 g PAMAM and dissolve it in 380-420 mL deionized water; adjust the stirrer speed to 140-160 rpm and stir gently at room temperature for 55-65 minutes until the solution is completely transparent and uniform;

[0020] Preparation of sulfonated graphene dispersion: Weigh 4.6-5.0 g of sulfonated graphene powder and add it to 380-420 mL of deionized water; first perform ultrasonic dispersion at 38-42 kHz for 55-65 minutes, then transfer the dispersion to a centrifuge tube, centrifuge at 4800-5200 rpm for 8-12 minutes, and carefully collect the supernatant to avoid disturbing the precipitate;

[0021] S6 Final Formula Mix

[0022] Transfer the prepared basic electroplating solution to a reactor of sufficient volume. Slowly add the solutions into the basic electroplating solution one by one in the order of PNIPAM solution, PAA solution, PANI dispersion, surfactant solution, silane solution, dendrimer solution, and sulfonated graphene dispersion. Maintain a stirring speed of 190-210 rpm during the entire addition process. After adding each component, add the next one after an interval of 8-12 minutes to ensure sufficient mixing; the total mixing time should be no less than 110 minutes;

[0023] After mixing, use a pH meter to monitor the pH of the solution, adjust the pH to 4.8-5.2 with dilute hydrochloric acid or potassium hydroxide solution, and then filter the entire system using a 4-6μm filter membrane. Let the filtered solution stand in a clean container for 11-13 hours. Before use, stir the solution again for 28-32 minutes to ensure that all components are fully uniform.

[0024] Furthermore, the amount of deionized water used is 5L.

[0025] Furthermore, the rotation speed of the stirrer is 300 rpm.

[0026] Furthermore, the ultrasonic frequency of the PNIPAM solution is 40 kHz.

[0027] Furthermore, the preparation temperature of the surfactant solution is 40°C.

[0028] Furthermore, the centrifugal speed of the sulfonated graphene dispersion is 5000 rpm.

[0029] Furthermore, the pH value of the final mixture is 5.0.

[0030] Furthermore, the standing time is 12 hours.

[0031] Furthermore, the stirring time before use is 30 minutes.

[0032] A second aspect of the present invention provides a tin plating additive, which is prepared according to the above-mentioned preparation method.

[0033] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present invention.

[0034] Beneficial technical effects of the present invention:

[0035] The present invention realizes a comprehensive improvement in coating performance by constructing a three-layer functional synergistic structure of an intelligent response layer, a self-assembly guide layer and an interface control layer. In the intelligent response layer, PNIPAM realizes a dynamic control interface of temperature response, PAA forms a stable chemical bond through a carboxyl functional group, and PANI constructs a three-dimensional conductive network to optimize current distribution; in the self-assembly guide layer, the surfactant forms an ordered molecular assembly to reduce the interface energy, and the silane coupling agent forms a networked silicon-oxygen bond structure to provide a chemical needle positioning point; in the interface control layer, the PAMAM dendritic molecule provides a large-area coordination site, and the sulfonated graphene forms a conductive network and provides active sites. This three-layer structure design not only improves the binding force through multiple chemical bonds, but also ensures the uniformity of the coating through precise control, and at the same time forms a dense protection to significantly improve the anti-corrosion performance. In terms of process, this product has the advantages of stable and controllable preparation process, reliable source of raw materials, compatibility with existing production lines and compliance with environmental protection requirements. It shows excellent coating performance indicators in practical applications, can effectively reduce the rework rate, extend the service life, has significant economic benefits, and can be widely used in multiple industrial fields. DETAILED DESCRIPTION

[0036] The optional embodiments of the present invention will be described in more detail below. Although the optional embodiments of the present invention are described, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0037] The terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0038] The present invention application provides a method for preparing a tin plating additive, comprising the following steps:

[0039] S1 Raw material preparation and inspection

[0040] Use an analytical balance to weigh the required raw materials: analytical pure stannous chloride, potassium chloride, and boric acid. Prepare deionized water with a conductivity of 0.05-0.15 μS / cm, and prepare functional components: PNIPAM powder with a molecular weight of 18000-22000, PAA aqueous solution with a mass fraction of 38-42%, doped PANI conductive powder, dodecyl dimethyl betaine, γ-aminopropyl triethoxysilane, PAMAM dendrimers, and sulfonated graphene powder with an oxidation degree of 28-32%;

[0041] S2 basic plating solution preparation

[0042] Clean and dry the 10L preparation tank. First, measure 4.8-5.2L of deionized water into the preparation tank. Turn on the agitator, adjust the speed to 280-320rpm, slowly add 380-420g of stannous chloride, observe the dissolution, and stir for 8-12 minutes until it is completely dissolved. Continue to add 950-1050g of potassium chloride, keep stirring at the same speed for 13-17 minutes, and after the potassium chloride is completely dissolved, add 130-150g of boric acid, continue stirring for 18-22 minutes until the solution is clear and transparent, and finally use deionized water to make up to 7.8-8.2L, and filter through a 0.45μm filter membrane to remove insoluble matter; the entire preparation process should be carried out at room temperature, and the dissolution should be observed regularly to avoid local precipitation;

[0043] Preparation of S3 intelligent response system

[0044] First, prepare the PNIPAM solution: prepare a 500 mL beaker, weigh 4.6-5.0 g of PNIPAM powder, slowly add 480-520 mL of deionized water, use a constant temperature magnetic stirrer to stir and swell at 190-210 rpm for 1.8-2.2 hours at room temperature. After swelling, transfer the solution to an ultrasonic processor and ultrasonicate at a frequency of 38-42 kHz for 28-32 minutes;

[0045] Next, prepare the PAA solution: Use a pipette to accurately measure 9.5-10.5 mL of PAA stock solution, slowly drop it into a beaker containing 470-510 mL of deionized water, and stir with a magnetic stirrer for 13-17 minutes until the solution is uniform and transparent;

[0046] Finally, PANI dispersion was prepared by weighing 3.0-3.4 g PANI powder, transferring it into a beaker containing 380-420 mL deionized water, and treating it with an ultrasonic disperser at a frequency of 38-42 kHz for 43-47 minutes, during which the dispersion state was observed every 15 minutes;

[0047] Preparation of S4 self-assembly guiding system

[0048] Preparation of surfactant solution: weigh 3.8-4.2 g of dodecyl dimethyl betaine, add 380-420 mL of deionized water, place the solution in a constant temperature water bath, control the temperature at 38-42 ° C, start the stirrer and stir for 18-22 minutes until the solution is completely clear;

[0049] Preparation of silane solution: In a fume hood, use a pipette to accurately measure 3.8-4.2 mL of γ-aminopropyltriethoxysilane, slowly drop it into 375-415 mL of anhydrous ethanol, adjust the stirrer speed to 140-160 rpm, and stir for 28-32 minutes for hydrolysis. During this period, pay attention to observe the state of the solution to avoid local gelation;

[0050] Preparation of S5 interface regulation system

[0051] Preparation of dendrimer solution: Weigh 4.6-5.0 g PAMAM and dissolve it in 380-420 mL deionized water; adjust the stirrer speed to 140-160 rpm and stir gently at room temperature for 55-65 minutes until the solution is completely transparent and uniform;

[0052] Preparation of sulfonated graphene dispersion: Weigh 4.6-5.0 g of sulfonated graphene powder and add it to 380-420 mL of deionized water; first perform ultrasonic dispersion at 38-42 kHz for 55-65 minutes, then transfer the dispersion to a centrifuge tube, centrifuge at 4800-5200 rpm for 8-12 minutes, and carefully collect the supernatant to avoid disturbing the precipitate;

[0053] S6 Final Formula Mix

[0054] Transfer the prepared basic electroplating solution to a reactor of sufficient volume. Slowly add the solutions into the basic electroplating solution one by one in the order of PNIPAM solution, PAA solution, PANI dispersion, surfactant solution, silane solution, dendrimer solution, and sulfonated graphene dispersion. Maintain a stirring speed of 190-210 rpm during the entire addition process. After adding each component, add the next one after an interval of 8-12 minutes to ensure sufficient mixing; the total mixing time should be no less than 110 minutes;

[0055] After mixing, use a pH meter to monitor the pH of the solution, adjust the pH to 4.8-5.2 with dilute hydrochloric acid or potassium hydroxide solution, and then filter the entire system using a 4-6μm filter membrane. Let the filtered solution stand in a clean container for 11-13 hours. Before use, stir the solution again for 28-32 minutes to ensure that all components are fully uniform.

[0056] 1. Core mechanism of action

[0057] This product achieves a comprehensive improvement in coating performance by constructing a three-layer functional synergistic structure. The innermost layer is the intelligent response layer, which is composed of three functional polymers: PNIPAM, PAA and PANI. During the electroplating process, the PNIPAM molecular chain undergoes a reversible conformational change with temperature changes, forming a dynamic control interface. This dynamic control effect can respond to temperature fluctuations during the electroplating process in real time and ensure the stability of the coating growth. At the same time, a large number of carboxyl functional groups on the PAA molecules form stable chemical bonds with the base metal through electrostatic and coordination effects, significantly enhancing the bonding force of the coating. PANI constructs a three-dimensional conductive network in this layer, optimizes the current distribution, and ensures the uniformity of the coating. The synergistic effect of the three components establishes a functionalized interface layer with intelligent response characteristics.

[0058] The middle self-assembly guiding layer is composed of surfactants and silane coupling agents. Dodecyl dimethyl betaine molecules spontaneously form ordered molecular assemblies at the interface, significantly reducing the interfacial energy and providing a good environment for the directional deposition of tin ions. γ-aminopropyl triethoxysilane forms a networked silicon-oxygen bond structure on the surface of the substrate through hydrolysis and condensation reactions, providing a large number of chemical pin positioning points. The synergistic effect of these two components not only provides stable chemical binding sites, but also forms a regular growth template, guiding the tin ions to deposit and crystallize in the expected direction.

[0059] The outermost interface control layer is composed of PAMAM dendritic molecules and sulfonated graphene. The unique dendritic structure of PAMAM molecules provides a huge specific surface area, and the abundant amino functional groups on its surface can form coordination with tin ions. Sulfonated graphene forms a continuous conductive network through its sheet structure and π-π stacking, and the sulfonic acid groups on its surface provide additional active sites. The role of this layer is to regulate the growth behavior of the coating and ensure the density and uniformity of the coating.

[0060] 2. Performance advantages and verification

[0061] This product has shown significant advantages through systematic performance testing. In terms of bonding strength, standard tensile testing has confirmed that the bonding strength of the coating has increased by 35-40% after adding this product. This improvement is due to the establishment of multiple chemical bonds, including coordination bonds, covalent bonds, and hydrogen bonds. Surface morphology analysis shows that the uniformity of the coating has increased by 40-45% and the surface roughness has been significantly reduced. This is due to the precise regulation of the deposition process by the smart response layer and the effective guidance of the growth behavior by the interface regulation layer.

[0062] In terms of anti-corrosion performance, the standard salt spray test verified that the corrosion resistance of the coating was improved by 2-3 levels, which was mainly due to the effective barrier of the dense three-layer functional structure to the corrosive medium. The conductivity test showed that the conductivity of the coating increased by 25-30%, which was the result of the combined effect of the conductive network constructed by PANI and sulfonated graphene.

[0063] 3. Process and application advantages

[0064] Another important advantage of this product is its good process adaptability. The process parameters of each step in the preparation process have been optimized and have good repeatability. All raw materials are commercially available products with stable sources and controllable costs. The product can be directly added to the existing tinning production line without the need to modify the equipment, and has strong practicality. At the same time, this product does not contain harmful substances such as heavy metals and meets environmental protection requirements.

[0065] In practical applications, this product has been piloted in the fields of automotive parts, building components, electronic components, etc. The results show that the coating thickness is controlled within the range of 15±2μm, the bonding force is ≥15MPa, and it exhibits excellent corrosion resistance in the 1000-hour salt spray test, with a surface roughness of Ra≤0.8μm. These indicators are better than traditional tin plating additives. Although the cost of this product is about 15% higher than that of traditional additives, the comprehensive economic benefits have been improved by more than 40% due to the significant improvement in coating quality, reduction in rework rate, and extension of service life.

[0066] In one embodiment of the present invention, the amount of deionized water used is 5L.

[0067] In one embodiment of the present invention, the rotation speed of the stirrer is 300 rpm.

[0068] In one embodiment of the present application, the ultrasonic frequency of the PNIPAM solution is 40 kHz.

[0069] In one embodiment of the present invention, the preparation temperature of the surfactant solution is 40°C.

[0070] In one embodiment of the present invention, the centrifugal speed of the sulfonated graphene dispersion is 5000 rpm.

[0071] In one embodiment of the present invention, the pH value of the final mixture is 5.0.

[0072] In one embodiment of the present invention, the standing time is 12 hours.

[0073] In one embodiment of the present invention, the stirring time before use is 30 minutes.

[0074] In one embodiment of the present invention, a tin plating additive is provided, and the additive is prepared according to the above-mentioned preparation method.

[0075] For the sake of clarity, the present invention is described in detail through the following embodiments (only the different parameters of each embodiment are listed).

[0076] Embodiment 1:

[0077] S1. Raw material preparation and inspection

[0078] Deionized water conductivity: 0.05μS / cm

[0079] PNIPAM molecular weight: 18000

[0080] Mass fraction of PAA aqueous solution: 38%

[0081] Sulfonated graphene oxidation degree: 28%

[0082] S2. Preparation of basic plating solution

[0083] Deionized water consumption: 4.8L

[0084] Stirring speed: 280rpm

[0085] Add 380g of stannous chloride, stir for 8 minutes Add 950g of potassium chloride, stir for 13 minutes Add 130g of boric acid, stir for 18 minutes Finally adjust the volume to 7.8L

[0086] S3. Preparation of intelligent response system

[0087] 1. PNIPAM solution:

[0088] PNIPAM powder: 4.6 g

[0089] Deionized water: 480 mL

[0090] Stirring speed: 190 rpm, swelling for 1.8 hours Ultrasonic frequency: 38 kHz, treatment for 28 minutes 2.PAA solution:

[0091] PAA stock solution: 9.5 mL

[0092] Deionized water: 470 mL

[0093] Mixing time: 13 minutes

[0094] 3. PANI dispersion:

[0095] PANI powder: 3.0g

[0096] Deionized water: 380 mL

[0097] Ultrasonic frequency: 38kHz, treatment for 43 minutes S4. Preparation of self-assembly guiding system 1. Surfactant solution:

[0098] Dodecyl dimethyl betaine: 3.8g

[0099] Deionized water: 380 mL

[0100] Temperature: 38℃

[0101] Mixing time: 18 minutes

[0102] 2. Silane solution:

[0103] γ-Aminopropyltriethoxysilane: 3.8 mL Anhydrous ethanol: 375 mL

[0104] Stirring speed: 140rpm

[0105] Hydrolysis time: 28 minutes

[0106] S5. Preparation of interface regulation system

[0107] 1. Dendrimer solution:

[0108] PAMAM: 4.6g

[0109] Deionized water: 380 mL

[0110] Stirring speed: 140rpm

[0111] - Mixing time: 55 minutes

[0112] 2. Sulfonated graphene dispersion:

[0113] Sulfonated graphene powder: 4.6g

[0114] Deionized water: 380 mL

[0115] Ultrasonic frequency: 38kHz, treatment for 55 minutes Centrifugal speed: 4800rpm, 8 minutes

[0116] S6. Final formulation mixing

[0117] Stirring speed: 190rpm

[0118] Interval between components: 8 minutes

[0119] Total mixing time: 110 minutes

[0120] pH adjustment range: 4.8

[0121] Standing time: 11 hours

[0122] Stirring time before use: 28 minutes

[0123] Example 2

[0124] S1. Raw material preparation and inspection

[0125] Deionized water conductivity: 0.10μS / cm

[0126] PNIPAM molecular weight: 20000

[0127] Mass fraction of PAA aqueous solution: 40%

[0128] Sulfonated graphene oxidation degree: 30%

[0129] S2. Preparation of basic plating solution

[0130] Deionized water consumption: 5.0L

[0131] Stirring speed: 300rpm

[0132] Add 400g of stannous chloride, stir for 10 minutes Add 1000g of potassium chloride, stir for 15 minutes Add 140g of boric acid, stir for 20 minutes Finally adjust the volume to 8.0L

[0133] S3. Preparation of intelligent response system

[0134] 1. PNIPAM solution:

[0135] PNIPAM powder: 4.8 g

[0136] Deionized water: 500 mL

[0137] Stirring speed: 200 rpm, swelling for 2.0 hours Ultrasonic frequency: 40 kHz, treatment for 30 minutes 2.PAA solution:

[0138] PAA stock solution: 10.0 mL

[0139] Deionized water: 490 mL

[0140] Mixing time: 15 minutes

[0141] 3. PANI dispersion:

[0142] PANI powder: 3.2g

[0143] Deionized water: 400 mL

[0144] Ultrasonic frequency: 40kHz, treatment for 45 minutes S4. Preparation of self-assembly guiding system 1. Surfactant solution:

[0145] Dodecyl dimethyl betaine: 4.0g

[0146] Deionized water: 400 mL

[0147] Temperature: 40℃

[0148] Mixing time: 20 minutes

[0149] 2. Silane solution:

[0150] γ-Aminopropyltriethoxysilane: 4.0 mL

[0151] Anhydrous ethanol: 395mL

[0152] Stirring speed: 150rpm

[0153] Hydrolysis time: 30 minutes

[0154] S5. Preparation of interface regulation system

[0155] 1. Dendrimer solution:

[0156] PAMAM: 4.8g

[0157] Deionized water: 400 mL

[0158] Stirring speed: 150rpm

[0159] Mixing time: 60 minutes

[0160] 2. Sulfonated graphene dispersion:

[0161] Sulfonated graphene powder: 4.8g

[0162] Deionized water: 400 mL

[0163] Ultrasonic frequency: 40kHz, treatment for 60 minutes

[0164] Centrifugation speed: 5000 rpm, 10 minutes

[0165] S6. Final formulation mixing

[0166] Stirring speed: 200rpm

[0167] Interval between components: 10 minutes

[0168] Total mixing time: 120 minutes

[0169] pH adjustment range: 5.0

[0170] Standing time: 12 hours

[0171] Stirring time before use: 30 minutes

[0172] Example 3

[0173] S1. Raw material preparation and inspection

[0174] Deionized water conductivity: 0.15μS / cm

[0175] PNIPAM molecular weight: 22000

[0176] Mass fraction of PAA aqueous solution: 42%

[0177] Sulfonated graphene oxidation degree: 32%

[0178] S2. Preparation of basic plating solution

[0179] Deionized water consumption: 5.2L

[0180] Stirring speed: 320rpm

[0181] Add 420g of stannous chloride, stir for 12 minutes Add 1050g of potassium chloride, stir for 17 minutes Add 150g of boric acid, stir for 22 minutes Finally adjust the volume to 8.2L

[0182] S3. Preparation of intelligent response system

[0183] 1. PNIPAM solution:

[0184] PNIPAM powder: 5.0 g

[0185] Deionized water: 520 mL

[0186] Stirring speed: 210 rpm, swelling for 2.2 hours Ultrasonic frequency: 42 kHz, treatment for 32 minutes 2.PAA solution:

[0187] PAA stock solution: 10.5 mL

[0188] Deionized water: 510 mL

[0189] Mixing time: 17 minutes

[0190] 3. PANI dispersion:

[0191] PANI powder: 3.4g

[0192] Deionized water: 420 mL

[0193] Ultrasonic frequency: 42kHz, treatment for 47 minutes S4. Preparation of self-assembly guiding system 1. Surfactant solution:

[0194] Dodecyl dimethyl betaine: 4.2g

[0195] Deionized water: 420 mL

[0196] Temperature: 42°C

[0197] Mixing time: 22 minutes

[0198] 2. Silane solution:

[0199] γ-Aminopropyltriethoxysilane: 4.2 mL

[0200] Anhydrous ethanol: 415mL

[0201] Stirring speed: 160rpm

[0202] Hydrolysis time: 32 minutes

[0203] S5. Preparation of interface regulation system

[0204] 1. Dendrimer solution:

[0205] PAMAM: 5.0g

[0206] Deionized water: 420 mL

[0207] Stirring speed: 160rpm

[0208] Mixing time: 65 minutes

[0209] 2. Sulfonated graphene dispersion:

[0210] Sulfonated graphene powder: 5.0g

[0211] Deionized water: 420 mL

[0212] Ultrasonic frequency: 42kHz, treatment time: 65 minutes

[0213] Centrifugation speed: 5200 rpm, 12 minutes

[0214] S6. Final formulation mixing

[0215] Stirring speed: 210rpm

[0216] Interval between components: 12 minutes

[0217] Total mixing time: 130 minutes

[0218] pH adjustment range: 5.2

[0219] Standing time: 13 hours

[0220] Stirring time before use: 32 minutes

[0221] Test Example 1

[0222] Control group formula (traditional tin plating additive)

[0223] Basic plating solution composition:

[0224] Stannous chloride: 80g / L

[0225] Potassium chloride: 200g / L

[0226] Boric acid: 30g / L

[0227] Traditional additive components:

[0228] Brightener A (N,N-diallylaniline): 1.5mL / L Brightener B (vanillin): 0.8mL / L

[0229] Carrier (polyethylene glycol 4000): 5g / L

[0230] Wetting agent (sodium dodecyl sulfate): 0.2g / L

[0231] The experimental group formula adopts Example 2 of the present invention to prepare the product.

[0232] 1. Binding strength test

[0233] Experimental methods

[0234] 1. Sample preparation:

[0235] Base material: Q235 steel plate (50mm×25mm×2mm), surface roughness Ra≤0.8μm

[0236] Pretreatment process:

[0237] Mechanical grinding (400, 800, 1200 sandpaper)

[0238] Alkali degreasing (50g / L NaOH, 60℃, 5min)

[0239] Acid activation (15% HCl, room temperature, 2 min)

[0240] Wash and dry

[0241] Electroplating process parameters:

[0242] Current density: 2.5A / dm 2

[0243] Temperature: 25±2℃

[0244] Time: 30 minutes

[0245] pH: 5.0±0.2

[0246] 2. Tensile test:

[0247] Instrument: WDW-100E electronic universal testing machine

[0248] Test conditions: 25±2℃, relative humidity 50±5%

[0249] Stretching rate: 2mm / min

[0250] Number of samples: 10 per group

[0251] Test Results

[0252] 1. Binding strength data:

[0253] Control group: 10.2±0.8MPa

[0254] Experimental group: 14.1±0.6MPa

[0255] Increase: 38.2%

[0256] 2. Fracture analysis:

[0257] Control group: 80% interfacial peeling, 20% mixed fracture

[0258] Experimental group: 95% matrix fracture, 5% mixed fracture

[0259] 2. Uniformity Test

[0260] Surface morphology analysis

[0261] 1.SEM observation:

[0262] Instrument: ZEISS SIGMA 500 field emission scanning electron microscope

[0263] Test parameters:

[0264] Accelerating voltage: 20 kV

[0265] Working distance: 15mm

[0266] Magnification: 1000×, 5000×, 10000×

[0267] Observation area: 5 points in the center and four corners of each sample

[0268] 2. Roughness test:

[0269] Instrument: Taylor Hobson Surtronic S128

[0270] Test parameters:

[0271] Sampling length: 0.8mm

[0272] Evaluation length: 4mm

[0273] Measuring speed: 0.5mm / s

[0274] Filtering: Gaussian filtering

[0275] Measuring points: 10 points / sample

[0276] Test Results

[0277] 1. Morphological characteristics:

[0278] Control group: grain size 3-8μm, uneven distribution, and agglomeration

[0279] Experimental group: grain size 2-4μm, uniform distribution, consistent orientation

[0280] 2. Roughness data:

[0281] Control group: Ra = 1.42 ± 0.15 μm, Rz = 6.8 ± 0.6 μm

[0282] Experimental group: Ra = 0.78 ± 0.08 μm, Rz = 3.9 ± 0.4 μm

[0283] Improvement: Ra decreased by 45.1%, Rz decreased by 42.6%

[0284] 3. Corrosion resistance test

[0285] Salt spray test

[0286] 1. Test conditions:

[0287] Equipment: YWX / Q-750 salt spray test chamber

[0288] Parameter settings:

[0289] Temperature: 35±2℃

[0290] Salt spray concentration: 5±0.5% NaCl

[0291] Spray volume: 1.5±0.5mL / 80cm 2 ·h

[0292] pH: 6.5-7.2

[0293] Detection cycle: 0h, 100h, 250h, 500h, 750h, 1000h

[0294] 2. Electrochemical test:

[0295] Instrument: CHI660E electrochemical workstation

[0296] Test system:

[0297] Working electrode: coating sample (1cm 2 )

[0298] Reference electrode: saturated calomel electrode

[0299] Auxiliary electrode: platinum sheet

[0300] Electrolyte: 3.5% NaCl

[0301] Test parameters:

[0302] Scan range: -1.5V~+0.5V

[0303] Scan rate: 0.5mV / s

[0304] Frequency range: 10-2~10 5 Hz

[0305] Test Results

[0306] 1. Salt spray test data:

[0307] Control group: red rust appears after 500 hours, and the rust area is >25% after 1000 hours Experimental group: only white rust appears after 1000 hours, and the rust area is <5%

[0308] Upgrade level: From protection level 6 to level 8

[0309] 2. Electrochemical parameters:

[0310] Corrosion potential (Ecorr):

[0311] Control group: -1.02V

[0312] Experimental group: -0.89V

[0313] Corrosion current density (icorr):

[0314] Control group: 8.6×10 -6 A / cm 2

[0315] Experimental group: 2.3×10 -6 A / cm 2

[0316] Impedance value (|Z|):

[0317] Control group: 2.1×10 3 Ω·cm 2

[0318] Experimental group: 7.8×10 3 Ω·cm 2

[0319] 4. Conductive performance test

[0320] Probe test

[0321] 1. Test conditions:

[0322] Instrument: RTS-9 four-probe tester

[0323] Parameter settings:

[0324] Test current: 100mA

[0325] Probe spacing: 1mm

[0326] Pressure: 100g

[0327] Test environment: 25±2℃, 50±5%RH

[0328] Measuring points: 3×3 dot matrix, 9 points in total

[0329] 2. Contact resistance test:

[0330] Instrument: TH2512B DC low resistance tester

[0331] Test parameters:

[0332] Test current: 1A

[0333] Pressure: 100g

[0334] Measuring points: 10 points / sample

[0335] Test Results

[0336] 1. Conductivity data:

[0337] Control group: 1.52×10 5 S / m

[0338] Experimental group: 1.98×10 5 S / m

[0339] Improvement: 30.3%

[0340] 2. Contact resistance:

[0341] Control group: 2.8±0.4mΩ

[0342] Experimental group: 1.9±0.2mΩ

[0343] Improvement: 32.1%

[0344] All test data were verified by three repeated experiments, the data reliability was good, and the test results showed significant statistical differences (P<0.05).

[0345] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made based on the present invention. Therefore, these modifications and improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.

Claims

1. A method for preparing a tin plating additive, characterized in that: The following steps are involved: S1 Raw material preparation and inspection Use an analytical balance to weigh the required raw materials: analytical grade stannous chloride, potassium chloride, and boric acid; Deionized water with a conductivity of 0.05-0.15 μS / cm is prepared, and functional components are prepared at the same time: PNIPAM powder with a molecular weight of 18000-22000, PAA aqueous solution with a mass fraction of 38-42%, doped PANI conductive powder, dodecyl dimethyl betaine, γ-aminopropyl triethoxysilane, PAMAM dendrimer molecules, and sulfonated graphene powder with an oxidation degree of 28-32%; S2 basic plating solution preparation Clean and dry the 10L preparation tank. First, measure 4.8-5.2L of deionized water into the preparation tank. Turn on the agitator, adjust the speed to 280-320rpm, slowly add 380-420g of stannous chloride, observe the dissolution, and stir for 8-12 minutes until it is completely dissolved. Continue to add 950-1050g of potassium chloride, keep stirring at the same speed for 13-17 minutes, and after the potassium chloride is completely dissolved, add 130-150g of boric acid, continue stirring for 18-22 minutes until the solution is clear and transparent, and finally use deionized water to make up to 7.8-8.2L, and filter through a 0.45μm filter membrane to remove insoluble matter; the entire preparation process should be carried out at room temperature, and the dissolution should be observed regularly to avoid local precipitation; S3 intelligent response system preparation First, prepare the PNIPAM solution: prepare a 500 mL beaker, weigh 4.6-5.0 g of PNIPAM powder, slowly add 480-520 mL of deionized water, use a constant temperature magnetic stirrer to stir and swell at 190-210 rpm for 1.8-2.2 hours at room temperature. After swelling, transfer the solution to an ultrasonic processor and ultrasonicate at a frequency of 38-42 kHz for 28-32 minutes; Next, prepare the PAA solution: Use a pipette to accurately measure 9.5-10.5 mL of PAA stock solution, slowly drop it into a beaker containing 470-510 mL of deionized water, and stir with a magnetic stirrer for 13-17 minutes until the solution is uniform and transparent; Finally, PANI dispersion was prepared by weighing 3.0-3.4 g PANI powder, transferring it into a beaker containing 380-420 mL deionized water, and treating it with an ultrasonic disperser at a frequency of 38-42 kHz for 43-47 minutes, during which the dispersion state was observed every 15 minutes; Preparation of S4 self-assembly guiding system Preparation of surfactant solution: weigh 3.8-4.2 g of dodecyl dimethyl betaine, add 380-420 mL of deionized water, place the solution in a constant temperature water bath, control the temperature at 38-42 ° C, start the stirrer and stir for 18-22 minutes until the solution is completely clear; Preparation of silane solution: In a fume hood, use a pipette to accurately measure 3.8-4.2 mL of γ-aminopropyltriethoxysilane, slowly drop it into 375-415 mL of anhydrous ethanol, adjust the stirrer speed to 140-160 rpm, and stir for 28-32 minutes for hydrolysis. During this period, pay attention to observe the state of the solution to avoid local gelation; Preparation of S5 interface regulation system Preparation of dendrimer solution: Weigh 4.6-5.0 g PAMAM and dissolve it in 380-420 mL deionized water; adjust the stirrer speed to 140-160 rpm and stir gently at room temperature for 55-65 minutes until the solution is completely transparent and uniform; Preparation of sulfonated graphene dispersion: Weigh 4.6-5.0 g of sulfonated graphene powder and add it to 380-420 mL of deionized water; first perform ultrasonic dispersion at 38-42 kHz for 55-65 minutes, then transfer the dispersion to a centrifuge tube, centrifuge at 4800-5200 rpm for 8-12 minutes, and carefully collect the supernatant to avoid disturbing the precipitate; S6 Final Formula Mix Transfer the prepared basic electroplating solution to a reactor of sufficient volume. Slowly add the solutions into the basic electroplating solution one by one in the order of PNIPAM solution, PAA solution, PANI dispersion, surfactant solution, silane solution, dendrimer solution, and sulfonated graphene dispersion. Maintain a stirring speed of 190-210 rpm during the entire addition process. After adding each component, add the next one after an interval of 8-12 minutes to ensure sufficient mixing; the total mixing time should be no less than 110 minutes; After mixing, use a pH meter to monitor the pH of the solution, adjust the pH to 4.8-5.2 with dilute hydrochloric acid or potassium hydroxide solution, and then filter the entire system using a 4-6μm filter membrane. Let the filtered solution stand in a clean container for 11-13 hours. Before use, stir the solution again for 28-32 minutes to ensure that all components are fully uniform.

2. The preparation method according to claim 1, characterized in that: The amount of deionized water used is 5L.

3. The preparation method according to claim 1, characterized in that: The rotation speed of the stirrer is 300 rpm.

4. The preparation method according to claim 1, characterized in that: The ultrasonic frequency of the PNIPAM solution is 40 kHz.

5. The preparation method according to claim 1, characterized in that: The preparation temperature of the surfactant solution is 40°C.

6. The preparation method according to claim 1, characterized in that: The centrifugal speed of the sulfonated graphene dispersion is 5000 rpm.

7. The preparation method according to claim 1, characterized in that: The pH of the final mixture was 5.

0.

8. The preparation method according to claim 1, characterized in that: The standing time is 12 hours.

9. The preparation method according to claim 1, characterized in that: The stirring time before use is 30 minutes.

10. A tin plating additive, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 9.